Computational Approach for Detection of Diabetes from Ocular Scans. (14th May 2022) - Khan, Asif Irshad; Kshirsagar, Pravin R.; Manoharan, Hariprasath; Alsolami, Fawaz; Almalawi, Abdulmohsen; Abushark, Yoosef B.; Alam, Mottahir; Chamato, Fekadu Ashine
Abstract : The estimated 30 million children and adults are suffering with diabetes across the world. A person with diabetes can recognize several symptoms, and it can also be tested using retina image as diabetes also affects the human eye. The doctor is usually able to detect retinal changes quickly and can help prevent vision loss. Therefore, regular eye examinations are very important. Diabetes is a chronic disease that affects various parts of the human body including the retina. It can also be considered as major cause for blindness in developed countries. This paper deals with classification of retinal image into diabetes or not with the help of deep learning algorithms and architecture. Hence, deep learning is beneficial for classification of medical images specifically such a complex image of human retina. A large number of image data are considered throughout the project on which classification is performed by using binary classifier. On applying certain deep learning algorithms, model results into the training accuracy of 96.68% and validation accuracy of 66.82%. Diabetic retinopathy can be considered as an effective and efficient method for diabetes detection.